Area-Selective Atomic Layer Deposition of ZnO on Si\SiO2 Modified with Tris(dimethylamino)methylsilane - Moeini, Behnam; Avval, Tahereh G; Brongersma, Hidde H; Průša, Stanislav; Bábík, Pavel; Vaníčková, Elena; Strohmeier, Brian R; Bell, David S; Eggett, Dennis; George, Steven M; Linford, Matthew R (Materials (Basel, Switzerland), 2023)
Delayed atomic layer deposition (ALD) of ZnO, i.e., area selective (AS)-ALD, was successfully achieved on silicon wafers (Si\SiO2) terminated with tris(dimethylamino)methylsilane (TDMAMS). This resist molecule was deposited in a home-built, near-atmospheric pressure, flow-through, gas-phase reactor. TDMAMS had previously been shown to react with Si\SiO2 in a single cycle/reaction and to drastically reduce the number of silanols that remain at the surface. ZnO was deposited in a commercial ALD system using dimethylzinc (DMZ) as the zinc precursor and H2O as the coreactant. Deposition of TDMAMS was confirmed by spectroscopic ellipsometry (SE), X-ray photoelectron spectroscopy (XPS), and wetting. ALD of ZnO, including its selectivity on TDMAMS-terminated Si\SiO2 (Si\SiO2\TDMAMS), was confirmed by in situ multi-wavelength ellipsometry, ex situ SE, XPS, and/or high-sensitivity/low-energy ion scattering (HS-LEIS). The thermal stability of the TDMAMS resist layer, which is an important parameter for AS-ALD, was investigated by heating Si\SiO2\TDMAMS in air and nitrogen at 330 °C. ALD of ZnO takes place more readily on Si\SiO2\TDMAMS heated in the air than in N2, suggesting greater damage to the surface heated in the air. To better understand the in situ ALD of ZnO on Si\SiO2\TDMAMS and modified (thermally stressed) forms of it, the ellipsometry results were plotted as the normalized growth per cycle. Even one short pulse of TDMAMS effectively passivates Si\SiO2. TDMAMS can be a useful, small-molecule inhibitor of ALD of ZnO on Si\SiO2 surfaces.
Keywords: silicon; silane; inhibitor; area selective; atomic layer deposition; ZnO